The Influence of Training Model Based on Exercise Assistance to The Skills of Smash Kedeng Sepakraw in The Pontianak City Athletes - Wiwik Yunitaningrum (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
The main problem of the research is whether there is an effect of the model of the stone-based smash training exercise on Pontianak City sepaktakraw athletes. The purpose of this study was to determine the effect of training models using tools to smash skills in Pontianak city athletes. Subjects were Pontianak athletes of 40 Pontianak athletes. The research method used is the True Experimental Design experiment. The type of True Experimental Design used was Pretest-posttest Control Group Design. Data collection was carried out by conducting a preliminary test of the Kedeng smash skill with a measurement tool for pool grabstart skill assessment, practice (training model using video media) and the final pool grabstart skill test. Data analysis and hypothesis testing using comparative analysis techniques using the Dependent sample t-test, namely Paired sample t-test and Independent sample t-test, namely t-Test: Two-Sample Assuming Equal Variances with a significant level α = 0.05. From the results of the hypothesis (t-test), the experimental group obtained a tcount of 9.67 with a t-distribution table at a significant level (∝) = 5% with a table of 2.101. It means tcount> ttable, 2.0101 there is a difference in the results of the smash skills in the post est and pretest in the experimental group. , 64% Calculation of gain score with a training model based on training aids gives an effect of 31.64% on the ability to smash.